Konsep Otoritas Alkitab di Hadapan Fakta Kesalahan Tekstual: Sebuah Diskusi Teologis - Yudi Jatmiko (Sekolah Tinggi Teologi SAAT (Southeast Asia Bible Seminary), 2017)
The field of Textual Criticism of the Bible has highlighted that various OT and NT manuscripts contain textual errors in the original apographs. These errors indicate a problem: in the face of various existing textual errors, does the Bible still have authority? Opponents of Biblical authority conclude that we cannot trust the text because of the serious nature of the textual problems. Proponents of Biblical authority take the opposite view and defend the authority of the Scriptures. Proponents argue that there is certainty regarding the meaning of the Bible despite its many textual errors. This is due to the fact that the textual changes do not significantly impact the meaning of the text. Additionally, the numerous textual variants of available manuscripts provide us with an inter-verifying process to ascertain the meaning of the text. Moreover, the impossibility of scribal conspiration signifies historical reference and value within the text. The certainty of the meaning of the text has implications for the certainty of biblical authority. Finally, the author concludes that though there are textual errors within the Bible they do not negate the authority of the Bible.